Serum enzymes and thyroid hormone in sub-clinical ketosis in goat and sheep reared under organized farming system - GUPTA, VINOD K; SHARMA, S D; VIHAN, V S; KUMAR, ASHOK (The Indian Journal of Animal Sciences, 2011)
Goats (514: Barbari, Jamunapari breed) and sheep (74: Muzaffanlagri breed) reared under organized fam1ing systenl were screened for pregnancy toxemia/lactational ketosis. In healthy goats and sheep, AST values decreased in pregnancy but increased during lactation, whereas ALT values increased both in pregnancy and lactation stages. Both AST and ALT values decreased in all animals affected \vith sub-clinical ketosis, but a significant decrease in ALT level was observed in Barbari goats during pregnancy. Serun1 thyroid hormone (T3 and T4) level marginally decreased in dry, pregnancy and lactation periods in Jamunapari, Barbari goats and Muzaffarnagri sheep, however, T4 level was significantly decreased in Barbari goats during pregnancy. Whereas in lactational ketosis, the values for T4 in Barbari goats were higher as compared to nonnaI healthy lactating goats. Serum cortisol values decreased in pregnancy and lactation in Barbari goats, whereas in Jamunapari goats values were slightly increased in pregnancy and decreased in lactation as compared to dry period. In sheep the values decreased, in dry, pregnancy and lactation period respectively. Cortisol level in Barbari goats was decreased (15.29%) but increased in sheep in lactational ketosis (23.11%).Â